Comparative Proteomics Reveals Evidence of Enhanced EPA Trafficking in a Mutant Strain of Nannochloropsis oculata - Wan Razali, Wan Aizuddin; Evans, Caroline A.; Pandhal, Jagroop (Frontiers in Bioengineering and Biotechnology, 2022)
The marine microalga, Nannochloropsis oculata is a bioproducer of fatty acid, eicosapentaenoic acid (EPA). EPA is incorporated into monogalactosyldiacylglycerol within N. oculata thylakoid membranes, and there is a biotechnological need to remodel EPA synthesis to maximize production and simplify downstream processing. In this study, a random mutagenesis and chemical-inhibitor-based selection method was devised to increase EPA production and accessibility for improved extraction. Ethyl methane sulfonate was used as the mutagen with selective pressure achieved by the use of two enzyme inhibitors of lipid metabolism; cerulenin and galvestine-1. Fatty acid methyl ester analysis of a selected fast-growing mutant strain had a higher percentage of EPA (37.5 % of total fatty acids) compared to the wild-type strain (22.2 % total fatty acids), with the highest EPA quantity recorded at 68.5 mg/g dry cell weight, while wild-type cells had 48.6 mg/g dry cell weight. Label-free quantitative proteomics for differential protein expression analysis revealed that the wild-type and mutant strains may have alternative channeling pathways for EPA synthesis. The mutant strain showed potentially improved photosynthetic efficiency, hence synthesizing a higher quantity of membrane lipids and EPA. The EPA synthesis pathways could also have deviated in the mutant, where fatty acid desaturase type 2 (13.7-fold upregulated) and lipid droplet surface protein (LDSP) (34.8-fold upregulated) were expressed significantly higher than the wild-type strain. This study increases understanding of EPA trafficking in N. oculata, leading to further strategies that can be implemented to enhance EPA synthesis in marine microalgae.